MPROVING STUDENTS’ WRITING SKILL ON DESCRIPTIVE PARAGRAPH THROUGH INSTAGRAM PERSONAL PHOTOGRAPHY AT THE 11th GRADE OF SMA PANGERAN ANTASARI MEDAN - Amaniarsih, Dwi Suci; Juliana, Juliana; Asrul, Nurmahyuni; Sijabat, Erni Darmayanti (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
This study's goal was to assess the writing skills of class XI SMA students. Regarding text descriptions, Pangeran Antasari. How does using a personal photo help students create better text descriptions? is how the issue is phrased. The purpose of this study was to teach secondary school pupils how to use real-world examples to improve their ability to create descriptive prose. Researchers employ the Classroom Action Research Methodology (CAR). 40 pupils from class XI made up the study's sample. The study's findings, which took into account both qualitative and quantitative data, showed that 90% of students could finish writing assignments once a discussion technique was applied. Data from cycles I and II were used to make this conclusion. In the pre-test, 17 students had a 42% success rate, while 23 students scored a 57.5 percent failure rate. 25 students completed cycle I with a success percentage of 62.5%, while 15 students failed with a rate of 37.5%. In cycle II, 36 students achieved a 90% success rate, while 10 students failed the post-test II with a 10% failure rate. Their writing skills greatly improved once the teaching and learning activities got going. It might be argued that using personal pictures helps pupils become better at producing descriptive text.Keywords : Personal photograph, descriptive text.